Building and Developing Digital Learning Literacy Skills during the Pandemic (Creating Computer- and Mobile-Based Learning Multimedia) at the Education Office Coordinator of Cisurupan District - Rahadian, Dian; Lay, Salfester; Astuti, Imas Nita; Diana, Eneng Nita (Indonesian Journal of Community Empowerment (IJCE), 2022)
This community service program was carried out to strengthen the capacity of teachers in the Cisurupan District Education Office in developing digital literacy skills during the COVID-19 pandemic, specifically through the design and use of computer- and mobile-based multimedia learning. The COVID-19 crisis accelerated the shift from conventional classroom practices to online learning, requiring teachers to master digital tools as an essential competence. A descriptive qualitative method was employed, combining workshops, interactive discussions, and hands-on practice, enabling teachers to gain direct experience in designing multimedia learning resources. The training materials included the use of applications such as Microsoft PowerPoint with interactive features, Canva for visual design, screen-recording software, and simple Android-based platforms for mobile learning. The results revealed a significant increase in teachers’ ability to integrate digital media into learning, not only from a technical perspective but also in terms of creativity and pedagogical innovation. Teachers were able to produce interactive learning content that improved student engagement, motivation, and independence in learning. However, challenges such as limited digital infrastructure, unstable internet connectivity, and the digital divide between teachers and students remained major issues. Despite these obstacles, the training successfully fostered confidence and readiness among teachers to adopt digital literacy as part of their professional development. The outcomes of this program emphasize that continuous mentoring, sustainable digital training, institutional support, and collaborative learning communities are crucial for ensuring the long-term success of digital literacy integration in education.